PERLINDUNGAN KORBAN TINDAK PIDANA PERKOSAAN SELAMA PROSES PERADILAN PIDANA - Ari Manik Wedani, Ni Putu; Satyayudha Dananjaya, Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2015)
Victims of rape often suffer severe trauma and humiliation of the crimes should be given legal protection, especially in search of justice in court. The problems are: what is the underlying importance of legal protection for the victims of the crime of rape? And how does the legal protection that can be given to victims of the crime of rape in facing the criminal trial process? The research method used is a juridical normative research through library research on the primary, secondary, and tertiary legal materials.The rationale of the need for legal protection for victims of crime of rape because the victim suffered both physically and psychologically, that it requires a considerable time of recovery, so by the time of the investigation and court trial processes, they need to get legal protection. The legal protection for the rape victims can be divided into three stages, namely: before, during, and after the court trials.
Keywords: Protection, Victim, Rape, Court Trial